Chronic vitamin D deficiency induces lung fibrosis through activation of the renin-angiotensin system - Shi, Yongyan; Liu, Tianjing; Yao, Li; Xing, Yujiao; Zhao, Xinyi; Fu, Jianhua; Xue, Xindong (Scientific reports, 2017)
Pulmonary fibrosis, which influences lung function and exacerbates a patient’s condition, is the ultimate stage of many lung diseases. Vitamin D deficiency is associated with pulmonary fibrosis and impaired lung function, but the underlying mechanism has not yet been fully elucidated. Moreover, vitamin D deficiency may cause over-activation of the renin-angiotensin system (RAS), which aggravates extracellular matrix (ECM) deposition and lung fibrosis. This study aims to investigate the effect of chronic vitamin D deficiency on lung fibrosis in otherwise healthy mice and to explore the role of RAS in this process. Mice were depleted of vitamin D through diet control and were compared with healthy subjects. Chronic vitamin D deficiency destructs lung structures, impairs lung development and stimulates ECM deposition. RAS components are also found to increase. These effects seem to worsen with prolonged vitamin D deficiency. By giving RAS blockers, these changes can be largely rescued. However, a smooth muscle relaxant whose regulatory effect on blood pressure is independent of RAS does not show similar effects. This study demonstrated that chronic vitamin D deficiency may induce RAS activation, which subsequently stimulates the expression of profibrotic factors and activates the fibrotic cascade. This profibrotic effect of RAS is independent of elevated blood pressure.